DOI: 10.33915/etd.1622
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of coalbed methane reservoir performance with type curves

Abstract: Coalbed methane is an unconventional gas resource that consists of methane production from the coal seams. CBM reservoirs are dual-porosity systems that are characterized by a complex interaction of coal matrix and cleat system that are coupled through desorption process. In order to effectively evaluate CBM resources, it necessary to utilize reservoir models that incorporate the unique flow and storage characteristics of CBM reservoirs. These models are often complicated to use, expensive, and time consuming.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Aminian and Ameri [2] derived a formula for calculating the peak gas rate based on the fluid radial flow equation. Bhavsar [8] estimated the dimensionless peak gas rate using a regression equation with critical gas desorption pressure, skin factor, porosity, Langmuir volume and Langmuir pressure. Zhou [45] developed equations to predict the peak gas rate, peak gas rate arrival time and decline rate by multiple regression of 200 simulations.…”
Section: Introductionmentioning
confidence: 99%
“…Aminian and Ameri [2] derived a formula for calculating the peak gas rate based on the fluid radial flow equation. Bhavsar [8] estimated the dimensionless peak gas rate using a regression equation with critical gas desorption pressure, skin factor, porosity, Langmuir volume and Langmuir pressure. Zhou [45] developed equations to predict the peak gas rate, peak gas rate arrival time and decline rate by multiple regression of 200 simulations.…”
Section: Introductionmentioning
confidence: 99%
“…Set of dimensionless rate and time were utilized by Bhavsar 20 to develop type curve for water. They do not require reservoir properties and they are presented as followed.…”
Section: Dimensionless Groups For Water Production Type Curvementioning
confidence: 99%
“…Arrey19 in 2004, evaluated the impact of Langmuir isotherm constants, gas production type curves.Arrey concluded that changes in V L values do not significantly impact the shape of the gas production type curves however; changes in P L values have a significant impact on the gas production type curves.Figure 2.11 shows the effect of P L changes on the CBM gas production type curves.Bhavsar20 in 2005 evaluated the impact of reservoir properties on the gas production type curves for Northern Appalachian. He also developed correlation for peak gas rate, correlation for initial (maximum) water rate, and dimensionless groups for water production type curves.…”
mentioning
confidence: 99%